Manajemen Kesehatan Menstruasi pada Remaja Sekolah Minggu GMIT Nazaret Oesapa Timur, Kota Kupang, Nusa Tenggara Timur - Windy Anisa Veryany Fanggi; Filpin Luciami A. Haning; Oktaviana T. M. B. Adam (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Reproductive health is an important aspect of adolescent development, including understanding menstrual health management. Limited access to information and reproductive health education often results in inadequate knowledge regarding menstrual hygiene, which may lead to various health problems. This community service activity aimed to improve adolescents' knowledge of Menstrual Health Management (MHM) among Sunday School adolescents at GMIT Nazaret Oesapa Timur, Kupang City, East Nusa Tenggara. The methods included an initial survey, health education through lectures and discussions, distribution of educational leaflets, and evaluation using pre-test and post-test assessments. The activity was conducted on January 18, 2026, involving 30 Sunday School adolescents. The pre-test results showed that 80% of participants had poor knowledge regarding menstrual health management. Following the educational intervention, the post-test results demonstrated a significant improvement, with 93.3% of participants achieving a good level of knowledge and no participants remaining in the poor knowledge category. These findings indicate that reproductive health education through counseling is effective in improving adolescents' understanding of menstrual health management. Support from Sunday School teachers also contributed to the successful implementation of the program. Continuous educational activities are recommended to further enhance adolescents' awareness and healthy behaviors related to reproductive health.